2018
DOI: 10.1002/jso.25242
|View full text |Cite
|
Sign up to set email alerts
|

Subungual melanoma: A retrospective cohort of 157 cases from Brazilian National Cancer Institute

Abstract: Background Subungual melanoma (SM) is rare. The lesions are thick at the time of diagnosis. Few studies have evaluated SM in Brazil. Objective The objective of this study was to investigate the factors associated with the survival of SM patients from the Brazilian National Cancer Institute. Methods One‐hundred and fifty‐seven patients diagnosed with SM were included in this study. We evaluated the epidemiologic, clinical, and histopathological data. Overall survival (OS) and relapse‐free survival (RFS) curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 32 publications
6
36
1
Order By: Relevance
“…The constitution percentages of different primary sites were consistent with the reports of Haugh et al and Curtin et al 12,17 With respect to age, the overall median age of the patients at time of diagnosis was 56 and the sole group had an older median/mean age than the other two groups, which is similar to another study result. 17 Nunes et al 10 analyzed 157 Brazilian AM patients; the age at diagnosis was older than ours and the age distribution between palms and nail beds was similar. This was not consistent with our comparison results.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…The constitution percentages of different primary sites were consistent with the reports of Haugh et al and Curtin et al 12,17 With respect to age, the overall median age of the patients at time of diagnosis was 56 and the sole group had an older median/mean age than the other two groups, which is similar to another study result. 17 Nunes et al 10 analyzed 157 Brazilian AM patients; the age at diagnosis was older than ours and the age distribution between palms and nail beds was similar. This was not consistent with our comparison results.…”
Section: Discussionmentioning
confidence: 46%
“…The stage III/IV distribution for the rest 2 groups were similar. Another study, 10 however, showed that the proportion of stage III/ IV in the palm group was threefold higher than that in the nail bed group, which may be due to race variation. The overall distant metastases percentage in our study was comparable with previous literature 2, 18 but the sole population had a higher proportion of distant metastases.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…An older German trial calculated a 5 year survival rate of 57% for SUM of the hand and 48% for tumors on the feet (Paul, Kleiner, & Bödeker, ). A recent large trial from Brazil observed 5 year OS and DFS rates of 61.0% and 41.8%, respectively (Nunes et al, ). In our series of patients, the median relapse‐free survival was 56 months and the median overall survival was 112.5 months.…”
Section: Discussionmentioning
confidence: 99%